Formation of Foamy Macrophages by Tuberculous Pleural Effusions Is Triggered by the Interleukin-10/Signal Transducer and Activator of Transcription 3 Axis through ACAT Upregulation - Genoula, Melanie; Marín Franco, José Luis; Dupont, Maeva; Kviatcovsky, Denise; Milillo, Ayelén; Schierloh, Pablo; Moraña, Eduardo Jose; Poggi, Susana; Palmero, Domingo; Mata-Espinosa, Dulce; González-Domínguez, Erika; León Contreras, Juan Carlos; et al. (Frontiers in Immunology, 2018)
The ability of Mycobacterium tuberculosis (Mtb) to persist in its human host relies on numerous immune evasion strategies, such as the deregulation of the lipid metabolism leading to the formation of foamy macrophages (FM). Yet the specific host factors leading to the foamy phenotype of Mtb-infected macrophages remain unknown. Herein, we aimed to address whether host cytokines contribute to FM formation in the context of Mtb infection. Our approach is based on the use of an acellular fraction of tuberculous pleural effusions (TB-PE) as a physiological source of local factors released during Mtb infection. We found that TB-PE induced FM differentiation as observed by the increase in lipid bodies, intracellular cholesterol and expression of the scavenger receptor CD36, as well as the enzyme acyl CoA:cholesterol acyl transferase (ACAT). Importantly, IL-10 depletion from TB-PE prevented the augmentation of all these parameters. Moreover, we observed a positive correlation between the levels of IL-10 and the number of lipid-laden CD14+ cells among the pleural cells in TB patients, demonstrating that FM differentiation occurs within the pleural environment. Downstream of IL-10 signaling, we noticed that the transcription factor STAT3 was activated by TB-PE, and its chemical inhibition prevented the accumulation of lipid bodies and ACAT expression in macrophages. In terms of the host immune response, TB-PE-treated macrophages displayed immunosuppressive properties and bore higher bacillary loads. Finally, we confirmed our results using BMDM from IL-10-/- mice demonstrating that IL-10 deficiency partially prevented foamy phenotype induction after Mtb lipids exposure. In conclusion, our results evidence a role of IL-10 in promoting the differentiation of FM in the context of Mtb infection, contributing to our understanding of how alterations of the host metabolic factors may favor pathogen persistence.